Wind Turbine Performance with Permanent Magnet Generator and Active Control (International Journal of Innovative Research in Computer Science & Technology, 2022)
Electricity's discovery and subsequent  expansion over the previous few hundred years have firmly  cemented its use and enhanced our dependency on it. This  is since it is the most basic and cost-effective technique of  carrying energy across large distances, and it is easy to  convert into other forms such as mechanical motion or  heat. As energy use rises and individuals who previously had access toelectricity become increasingly prepared to  engage in the energy market, certain challenges arise. New  infrastructure cannot be built in a place that is too remote  from existing infrastructure and has a small population. In  this situation, renewable energy sources such as micro hydro (if available),solar, and wind are the next best  options. As the globe attempts to attain a carbon-neutral  goal to minimize future damage caused by the use of fossil  fuels, renewable energy sources are gaining in favor. This  study provides a plausible idea for a tiny wind-powered  microgrid for a small population in windy environments  including mountainous regions and natural wind paths like  valleys and mountain passes, large plains, and ocean  locations, among others.
Keywords: Microgrid; Domestic Wind Turbine; Fossil Fuels